Intelligent Silk Fibroin Based Microneedle Dressing (i‐SMD). (21st October 2020) - Gao, Bingbing; Guo, Maoze; Lyu, Kai; Chu, Tianshu; He, Bingfang
Abstract: Wounds, especially those caused by chronic diseases, are severe threats to human health. To facilitate their recovery, considerable efforts have been devoted to the generation of wound tissues and the detection of wound biomarkers. Here, an intelligent origami silk fibroin microneedle‐structured dressing (i‐SMD) with a smart drug release system, biochemical sensing, and physiological monitoring ability for epidermal sensing and wound healing, is presented. By utilizing temperature‐responsive N ‐isopropylacrylamide (NIPAM) hydrogel and inverse opal (IO) photonic crystals (PCs) as a smart drug release system, controllable drug release is achieved on the i‐SMD. The patterned microfluidic channels on the i‐SMD and IO PCs enable the liquid to flow spontaneously in the channels, thereby achieving sensitive multiple biochemical analysis of inflammatory factors; meanwhile, microelectronic circuits integrated on the i‐SMD enable sensitive motion monitoring. Notably, the performance of i‐SMD in facilitating wound healing is demonstrated by treating full‐thickness cutaneous wounds in a diabetic mouse model, indicating the remarkable prospects of i‐SMD in wound management and other related biomedical fields. Abstract : Intelligent silk fibroin‐based microneedle dressing (i‐SMD) with photonic crystals, microfluidics, and microelectro circuits are fabricated by simply duplicating negative molds. The intelligent and highly integrated i‐SMD with electro‐microfluidics and smart drug release systems enable sensitive biochemical and physiological sensing. It could also serve as an intelligent dressing for facilitating wound healing.